Synthesis, Characterization and Biological Activity of New Mefenamic acid - Oxoazetidine Derivatives - Ayad M.R. Raauf (College of Pharmacy / Mustansiriyah University, 2013)
Several new oxoazetidine derivatives based on mefenamic acid were synthesized via a four steps method in good yields.1st step was prepared 2-[2-chloro-N-(2,3- dimethylphenyl)acetamido]benzoic acid (2) by condensation of mefenamic acid with chloroacetyl chloride, which on amination with hydrazine hydrate in ethanol to give 2-[N- (2,3-dimethylphenyl)-2-hydrazinylacetamido] benzoic acid (3) in good yields(2nd step). Compound 3, on condensation with various aldehydes afforded a series of Schiff bases 2-[N- (2,3-dimethylphenyl)-2-(2-arylhydrazinyl)acetamido]benzoic acid (4a-f) (3rd step). A series of oxoazetidine have been synthesized by cyclocondensation of various Schiffm bases (4a-f) with chloroacetyl chloride or phenyl acetyl chloride in presence of triethyl amine to yield compounds (5a-f) and (6a-f), respectively (4th step). Purified compounds were characterized by mp, TLC, UV, FT-IR and elemental analysis. The synthesized compounds (5a-f) were screened for their antibacterial activities against three species of bacteria. They were found to exhibit good antibacterial activity.